APC-resistance Is a Risk Factor for Postoperative Thromboembolism in Elective Replacement of the Hip or Knee – A Prospective Study - Lindahl, Tomas L.; Lundahl, Tom H.; Nilsson, Lennart; Andersson, Christer A. (Thrombosis and Haemostasis, 1999)
Postoperative venous thromboembolic complications are commonly seen after total replacement of the hip or knee. Recently, an inherited defect with resistance to the anticoagulant activity of activated protein C (APC-resistance) has been detected. APC-resistance seems to be a common risk factor, especially in Sweden, and it increases the propensity for venous thrombosis. This study assesses the prevalence of APC-resistance in a general population and its clinical significance for patients undergoing surgery associated with a high risk of thromboembolic complications. In a prospective cohort study, we analysed for APC-resistance in 645 consecutive patients before elective replacement of the hip or knee at 3 hospitals in southern Sweden. Thromboprophylaxis with LMWH-heparin was given to all patients throughout the hospitalisation period. We recorded events of clinical thromboembolism for 3 months postoperatively. Venography, ultrasonography or pulmonary scintigraphy was requested by the clinicians according to the existing routines, i.e. only patients with symptoms of thromboembolism were examined. A thromboembolic complication was registered in 20 (3.1%) patients. Fifty per cent of the venous thrombi had a proximal location. Only 0.3% of the patients had verified pulmonary embolism. APC-resistance was found in 14.1% of the patients, of whom 9.9% had experienced postoperative thromboembolism compared with 2.0% of the patients without APC-resistance (p <0.0007). We conclude that APC-resistance is a frequent risk factor for symptomatic postoperative deep venous thrombosis with an estimated relative risk of 5.0 (95% confidence interval: from 1.9 to 12.9) in elective replacement of the hip or knee.